2008
DOI: 10.1177/0269881108094722
|View full text |Cite
|
Sign up to set email alerts
|

Early onset anxiolytic efficacy after a single dose of pregabalin: double-blind, placebo- and active-comparator controlled evaluation using a dental anxiety model

Abstract: To evaluate acute onset of anxiolytic activity using a dental anxiety model, 89 patients were randomised to double-blind single dose pregabalin 150 mg, alprazolam 0.5 mg or placebo 4 h before a scheduled dental procedure. A Dental Anxiety Total score >12 (moderate-to-severe) without meeting Diagnostic and Statistical Manual of Mental Disorders (Fourth edition) (DSM-IV) anxiety disorder criteria was required. Efficacy and safety, assessed 2, 2.5, 3, 3.5 and 4 h postdose, included 100 mm Visual Analogue Scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 22 publications
3
25
0
8
Order By: Relevance
“…Interestingly, pregabalin present a rapid anxiolytic effect (Nutt et al 2009), similar to the effect presented in this work. While pregabalin can decrease the release of glutamate (Martinotti et al 2013), ascorbic acid can impair the glutamate binding to the NMDA receptor (Majewska et al 1990).…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, pregabalin present a rapid anxiolytic effect (Nutt et al 2009), similar to the effect presented in this work. While pregabalin can decrease the release of glutamate (Martinotti et al 2013), ascorbic acid can impair the glutamate binding to the NMDA receptor (Majewska et al 1990).…”
Section: Discussionsupporting
confidence: 87%
“…These results raise the question of whether pregabalin might have an anxiolytic effect within the first hours after a single-dose administration by contrast with the efficacy demonstrated during long-term treatment of generalized anxiety disorder. 4,5 Nutt et al 25 have found that a preoperative dose of pregabalin 150 mg provided a clinically meaningful anxiolytic effect within 4 h of intake, although the speed of response was not as rapid as it was after administration of alprazolam, an active placebo. The difference among the aforementioned studies relies on the fact that Nutt et al 25 have evaluated patients' anxiety for several hours after pregabalin intake, whereas in the negative studies, 15,24 the authors have assessed anxiety state only at 1 h after pregabalin administration.…”
Section: Pain Medicinementioning
confidence: 99%
“…9 Relative to SSRIs or SNRIs, pregabalin may have an early onset of effect: a study in healthy volunteers found anxiolytic effects within 3e4 h following a single dose. 10 It is generally well tolerated with few drug interactions and a low rate of discontinuation symptoms, and can prevent relapse over 24 weeks. 11 Sleep disturbance is common in GAD, and pregabalin reduces sleep disturbance, both directly, and indirectly via the reduction of anxiety.…”
Section: Managementmentioning
confidence: 99%